2015
DOI: 10.1186/s13012-016-0480-9
|View full text |Cite
|
Sign up to set email alerts
|

Implementing shared decision-making: consider all the consequences

Abstract: BackgroundThe ethical argument that shared decision-making is “the right” thing to do, however laudable, is unlikely to change how healthcare is organized, just as evidence alone will be an insufficient factor: practice change is governed by factors such as cost, profit margin, quality, and efficiency. It is helpful, therefore, when evaluating new approaches such as shared decision-making to conceptualize potential consequences in a way that is broad, long-term, and as relevant as possible to multiple stakehol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
271
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 339 publications
(281 citation statements)
references
References 43 publications
5
271
0
5
Order By: Relevance
“…Additionally, this systematic review adhered to the PRISMA guidelines, [43,44] and the internal validity of the included studies was rated as acceptable or high. Finally, findings in cancer care were consistent with those reported across other disease areas, [23,28,49] indicating that the lack of qualitative and quantitative assessment of SDM interactions is not unique to cancer care and needs to be considered broadly across future SDM intervention studies.…”
Section: Limitationssupporting
confidence: 71%
See 2 more Smart Citations
“…Additionally, this systematic review adhered to the PRISMA guidelines, [43,44] and the internal validity of the included studies was rated as acceptable or high. Finally, findings in cancer care were consistent with those reported across other disease areas, [23,28,49] indicating that the lack of qualitative and quantitative assessment of SDM interactions is not unique to cancer care and needs to be considered broadly across future SDM intervention studies.…”
Section: Limitationssupporting
confidence: 71%
“…Outcomes that were more distal to the intervention or decision-such as changes in symptoms, HRQoL, or functional status and well-being-were infrequently assessed, usually did not achieve statistical significance, and may indicate that study designs focused on a single patient-clinician interaction are not well suited to capturing outcomes outside of immediate decision making. Given that more distal outcomes are often most relevant to patients themselves and represent key indicators of high quality of care, [49] optimal study designs for longitudinal (multiple-touch point) SDM interventions as well as measuring more distal outcomes are an area in need of further research. Furthermore, the lack of consistency in the tools used to assess the 81 unique outcomes identified in this study complicates comparisons across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While few in number, implementation studies on SDM interventions in Sweden have suggested the importance of expanding the decision-making process beyond single encounters (Hultberg & Rudebeck, 2017) and beyond simply educating the patient in self-care (Herlitz, Munthe, Törner, & Forsander, 2016). Results from somatic care studies suggest that successful implementation of SDM requires continuity of care and that the user is offered concrete opportunities to participate as an equal in the decision-making process (Elwyn, Frosch, & Kobrin, 2015). Basic prerequisites for successful implementation of SDM in psychiatric care settings are considered to consist of the following factors; (a) attending staff have the ability and are willing to include the user in decisions (skills and attitude) (b) the user is willing and has the ability to actively participate in the decisions (c) additional information and decision support is available to facilitate the SDM process (Hamann, Kruse, Schmitz, Kissling, & Pajonk, 2010; O’Connor et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of decision-making in healthcare is to choose the interventions that are most likely to deliver the outcomes that are of most interest to patients while preventing possible harmful outcomes [134]. With this manuscript, the aim was to demonstrate that laser-technology is in far expansion within the endodontic field and that with double-wavelength lasers, clinicians should expect to achieve highly predictable outcomes and less iatrogenic complications even in the most complicated endodontic scenarios such as in multi-rooted teeth with unfavourable anatomies, associated with AP.…”
Section: Resultsmentioning
confidence: 99%